Semiotics Study: A Meaning Analiysis Of The Lyrics Of The Song “Tablo Kasmaran” By Eutik Muchtar - Maulana, Marsel Ridky; Mugiyat , Arellya; Budiman , Nandang; Taswadi, Taswadi (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
TThis study aims to explore the deep meaning of the lyrics of the song “Tablo Kasmaran” by Eutik Muchtar, which is popular in Kliningan and Wayang Golek arts. Using a qualitative approach, this study utilizes Riffaterre's semiotic theory to explore the layers of meaning contained in the lyrics. The song “Tablo Kasmaran” is known for its outstanding musicality and evocative lyrics, making it an interesting object of research. Through this analysis, the author uncovers a hidden message, the song conveys a feeling of the heart that reminds one of waiting in solitude, of the emptiness that can only be filled by the one who is missed. Each stanza takes us on a deep emotional journey from longing, heartache, to the point of accepting that a loved one may not return. The findings of this research are expected to provide a deeper insight into the meaning and cultural values in Sundanese music, as well as a contribution to the study of local music semiotics.